Determinants of gestational syphilis among women attending prenatal care programs in the Brazilian Amazon - Uchôa, Thais Lopes do Amaral; Araújo, Eliete da Cunha; da Silva, Richardson Augusto Rosendo; Valois, Rubenilson; Azevedo Junior, Wanderson Santiago de; Nascimento, Valéria Gabriele Caldas; Aben-Athar, Cintia Yolette Urbano Pauxis; Parente, Andressa Tavares; Botelho, Eliã Pinheiro; Ferreira, Glenda Roberta Oliveira Naiff (Frontiers in Public Health, 2022)
Background: There are high proportion of pregnant women who were attending antenatal care who were not tested for syphilis or tested but not treated, among priority countries. The coverage antenatal care visit, syphilis screening and treatment are priority indicators for monitoring of the elimination. The aim to determine the factors associated with gestational syphilis among postpartum women who were on antenatal care program, in the brazilian Amazon. Methods: unmatched case–control study , was conducted at the hospital, in the Brazil. Data collection was carried out from November 2020 to July 2021, during hospitalization using a pretested structured questionnaire. The criteria for selection of cases and control followed the established by the Ministry of Health of Brazil: postpartum women with registry of laboratory diagnosis based on treponemal and/or nontreponemal tests, symptoms of syphilis or asymptomatic, treatment or not treated and on antenatal care program. Gestational syphilis cases were women who tested positive for syphilis and those who tested negative were controls, at the least one antenatal care visit, childbirth and/or the puerperium. Was estimated a sample size of 59 cases and 118 controls (1: 2 ratio of cases to controls). Data were analysed using Minitab 20® and Bioestat 5.3® software. The odds ratiowas calculated by multiple logistic regression. Results: One hundred and seventy-seven postpartum women were included in the study, 59 cases and 118 controls. Among all participants, 95.5% (169) were tested for syphilis in any trimester during pregnancy and at the delivery and 4.5% (8) were tested in the maternity only, at the time childbirth and/or puerperium.The final multiple logistic regression model evidenced that cases had higher odds compared to controls: past history of sexually transmitted infections (AOR: 55.4; p: 0.00), difficulty talking about condom use with sexual partner (AOR: 4.92; p: 0.01), one to six prenatal care visits(AOR: 4.93; p: 0.01), not received sexually transmitted infections test result in the maternity hospital (AOR: 4.09; p: 0.04), lower monthly income (AOR: 4.32; p: 0.04), one to three of miscarriage (AOR: 4.34; p: 0.01). Conclusion: The sociodemographic, programmatic, obstetric and sexual factors are associated with gestational syphilis among postpartum women.